Politics in Harold Pinter's One for the Road (Journal of the College of Education for Women, 2019)
Pinter's play One for the Road (1984) is considered one of his important plays becauseit focuses on political issues, which he has not presented overtly before. Generally speaking,Pinter's early plays describe man's existential fear of an unnamed danger which might berepresented by an intruder who invades the characters' solitude , threatens their peace, andbrings their hidden fears to the surface. Pinter began to write political plays as a result of hispolitical attitudes and his involvement in political activities over the last three decades.Pinter's One for the Road deals with the oppressive and authoritarian operations ofstate power. This play and Pinter's political plays which followed it, like MountainLanguage(1988), Party Time(1991),and Ashes to Ashes (1997)were greeted by reviewers andcritics alike as signaling a shift in his career and showing his concern with the more publicterrain of politics.In One for the Road, Pinter presented a character that is accused of an unnamed crimeby an unnamed government and that is exposed to physical and psychological torture.Through the play, Pinter criticized modern political systems which he accused them ofpracticing similar ways of torture.The present study throws light on Pinter's One for the Road as a political play.Besides, it explores Pinter's political views and how they contributed to making a shift in histheatrical career. Part one of the study deals briefly with Pinter's early plays. Part two dealswith his political activism and part three is an elaborate discussion of Pinter's One for theRoad as a political play.